A new role for histone deacetylase 5 in the maintenance of long telomeres. Issue 9 (31st May 2013) - Novo, Clara Lopes; Polese, Catherine; Matheus, Nicolas; Decottignies, Anabelle; Londono‐Vallejo, Arturo; Castronovo, Vincent; Mottet, Denis
Abstract : Telomeres are major regulators of genome stability and cell proliferation. A detailed understanding of the mechanisms involved in their maintenance is of foremost importance. Of those, telomere chromatin remodeling is probably the least studied; thus, we intended to explore the role of a specific histone deacetylase on telomere maintenance. We uncovered a new role for histone deacetylase 5 (HDAC5) in telomere biology. We report that HDAC5 is recruited to the long telomeres of osteosarcoma‐ and fibrosarcoma‐derived cell lines, where it ensures proper maintenance of these repetitive regions. Indeed, depletion of HDAC5 by RNAi resulted in the shortening of longer telomeres and homogenization of telomere length in cells that use either telomerase or an alternative mechanism of telomere maintenance. Furthermore, we present evidence for the activation of telomere recombination on depletion of HDAC5 in fibrosarcoma telomerase‐positive cancer cells. Of potential importance, we also found that depletion of HDAC5 sensitizes cancer cells with long telomeres to chemotherapeutic drugs. Cells with shorter telomeres were used to control the specificity of HDAC5 role in the maintenance of long telomeres. HDAC5 is essential for the length maintenance of long telomeres and its depletion is required for sensitization of cancer cells with long telomeres to chemotherapy. —Novo, C. L., Polese, C., Matheus, N., Decottignies, A., Londono‐Vallejo, A., Castronovo, V., Mottet, D., A new role for histone deacetylase 5 in the maintenance of long telomeres. FASEB J. 27, 3632–3642 (2013). www.fasebj.org